Bridging Zirconia Nodes within a Metal–Organic Framework via Catalytic Ni-Hydroxo Clusters to Form Heterobimetallic Nanowires - Platero-Prats, Ana E; League, Aaron B; Bernales, Varinia; Ye, Jingyun; Gallington, Leighanne C; Vjunov, Aleksei; Schweitzer, Neil M; Li, Zhanyong; Zheng, Jian; Mehdi, B. Layla; Stevens, Andrew J; Dohnalkova, Alice; et al. (Journal of the American Chemical Society, 2017)
Metal–organic frameworks (MOFs), with their well-ordered pore networks and tunable surface chemistries, offer a versatile platform for preparing well-defined nanostructures wherein functionality such as catalysis can be incorporated. Notably, atomic layer deposition (ALD) in MOFs has recently emerged as a versatile approach to functionalize MOF surfaces with a wide variety of catalytic metal-oxo species. Understanding the structure of newly deposited species and how they are tethered within the MOF is critical to understanding how these components couple to govern the active material properties. By combining local and long-range structure probes, including X-ray absorption spectroscopy, pair distribution function analysis, and difference envelope density analysis, with electron microscopy imaging and computational modeling, we resolve the precise atomic structure of metal-oxo species deposited in the MOF NU-1000 through ALD. These analyses demonstrate that deposition of NiO x H y clusters occurs selectively within the smallest pores of NU-1000, between the zirconia nodes, serving to connect these nodes along the c-direction to yield heterobimetallic metal-oxo nanowires. This bridging motif perturbs the NU-1000 framework structure, drawing the zirconia nodes closer together, and also underlies the sintering resistance of these clusters during the hydrogenation of light olefins.